Occurrence of glyphosate in surface and drinking water sources in Cúcuta, Norte de Santander, and its removal using membrane technology - Álvarez Bayona, María Angélica; Maturana Córdoba, Aymer; Gallardo Amaya, Romel J.; Muñoz Acevedo, Amner (Frontiers in Environmental Science, 2022)
Glyphosate is currently the herbicide with the highest use worldwide for weed control, it has been detected in different water sources, including drinking water, which could be generating potential damage to human health. In the Metropolitan area of Cucuta, intensive rice cultivation is predominant and, as it grows in flooded areas, the use of herbicides has greater contact with water bodies, which are used as sources of supply. Based on this, the concentration of glyphosate was quantified in five sampling points of surface and drinking water of the Pamplonita and Zulia rivers, using UV/VIS spectrophotometry; establishing that the concentration found in drinking water (216 and 204.5 µg/L) was below the maximum allowable limits of countries such as the United States, Canada and Australia; and above those of the European Union and the United Kingdom. Once the occurrence was identified, the removal capacity of glyphosate was evaluated using membrane technology through Reverse Osmosis (RO) and Nanofiltration (NF) in a pilot plant, for which response surface optimization models were implemented, and 100 % removals were obtained; with a repeatability close to 1 % with respect to other reported investigations, highlighting that the NF process was more efficient even though the molecular weight of glyphosate was below the limit of the membrane. On the other hand, it was determined that according to the concentrations found in the drinking water supplied to the metropolitan area of Cucuta, this has a low risk according to the guidelines for drinking water quality in Canada and moderate risk according to the World Health Organization (WHO). That the conventional systems currently used for water purification are insufficient to remove traces of contaminants such as herbicides, and therefore it is necessary to implement new technologies.